Clinical comparative study of glasses-free 3D and 2D thoracoscopic surgery in minimally invasive esophagectomy - Wei, Rongqiang; Ding, Xinyu; Chen, Zihao; Xin, Ning; Liu, Chengdong; Fang, Yunhao; Xu, Zhifei; Huang, Kenan; Tang, Hua (Frontiers in Oncology, 2022)
Objective To investigate the safety and efficacy of glasses-free 3D thoracoscopic surgery in minimally invasive esophagectomy（MIE）. Methods Clinical data of 98 patients, including 81 males and 17 females aged 45-77 years, with esophageal squamous cell carcinoma who underwent minimally invasive thoracoscopic esophagectomy from January 2017 to December 2019 (3 years, with clinical follow-up time:1 year~4 years（2017.01-2020.12）) were retrospectively analyzed. Patients were divided into two groups according to different surgical methods including a glasses-free 3D thoracoscopic group (G-3D group: 38 patients) and a 2D thoracoscopic group (2D group: 60 patients). The clinical outcome of the two groups were compared. Results The operation time of thoracoscopic part in G-3D group was significantly shorter than that in the 2D group (P<0.05). The total number of lymph nodes dissection in G-3D group was more than that in the 2D group (P<0.05). The thoracic indwelling time, postoperative hospital stay, severe pulmonary infection, arrhythmia, anastomotic leakage, chylothorax, and recurrent laryngeal nerve injury were not significantly different between the two groups (P>0.05). There was also no significant difference between the two groups on the progress free survival (PFS) (P>0.05). Conclusion Glasses-free 3D thoracoscopic surgery for esophageal cancer is a safe and effective surgical procedure. Compared with the 2D thoracoscopic MIE, the glasses-free 3D thoracoscopic MIE for esophageal cancer have higher safety, more lymph nodes dissection and higher operation efficiency through the optimized surgical operations. We believe that the glasses-free 3D thoracoscopy for MIE is worthy of clinical promotion.